Analyzing Remanufacturability of Mobile Phones using DEMATEL Approach - Gan Shu San (Jurnal Teknik Industri, 2019)
The use of mobile phone has increased at a surprisingly high rate over these two decades.  For many people, especially young generations, mobile phone has even become a primary need. As a consequence, the production of mobile phone has increased significantly and followed immediately by the disposal, as a result of its short life-cycle nature. Recently, there are substantial initiatives proposed in order to mitigate the effect of e-waste to the environment. Remanufacturing is one of recovery processes that could extend product’s useful life, and provide a circular life-cycle instead of linear. However, there are many factors that can affect the success of remanufacturing engagement, and specifically remanufacturability of a mobile phone. There are numerous considerations of remanufacturability with regards to the short life-cycle nature of mobile phone, and these factors can be qualitative or quantitative, with conflicting potentials, and some of them may be uncertain. In this study, we use Decision Making Trial and Evaluation Laboratory (DEMATEL) approach to identify the interrelationship among the factors, and analyze those results to identify the prominent factors. Furthermore, an influential-relation map is provided to support visualization for managerial implications.